Differences in trunk and thigh muscle strength, endurance and thickness between elite sailors and non-sailors - Friesenbichler, B.; Item-Glatthorn, J. F.; Neunstöcklin, F.; Casartelli, N. C.; Guilhem, G.; Maffiuletti, N. A. (Sports Biomechanics, 2018)
Dinghy sailors lean their upper body over the windward side of the boat (`hiking`) to keep the boat`s balance and maximise its speed. Sustaining the hiking position is essential for competitive performance and this study examined sport-specific differences of muscles relevant for hiking in elite sailors. Knee extensor muscle strength as well as trunk muscle strength, muscle endurance and muscle thickness were assessed in elite dinghy sailors (n = 15) and compared to matched, non-sailing controls (n = 15). Isometric extensor strength was significantly higher in sailors at 60° (+14%) but not at 20° knee flexion. Sailors showed significantly higher trunk flexor (but not extensor) strength under isometric (+18%) and eccentric (+11%) conditions, which was associated to greater muscle thickness (rectus abdominis +40%; external oblique +26%) and higher endurance for ventral (+66%) and lateral (+61%) muscle chains compared to non-sailors. Greater muscles thickness and the particular biomechanical requirements to maintain the hiking position may drive the increases in isometric and eccentric muscle strength as well as ventral and lateral trunk endurance. The current findings identified sport-specific muscle function differences and provide performance benchmarks for muscle strength and endurance in elite sailors. ABSTRACT FROM AUTHOR